Resistance trained athletes using or not using anabolic steroids compared to runners: effects on cardiorespiratory variables, body composition, and plasma lipids. Issue 1 (March 1996) - Yeater, R; Reed, C; Ullrich, I; Morise, A; Borsch, M
Abstract : OBJECTIVE–To determine whether there is a difference in cardiac size and function as well as in body composition, aerobic capacity, and blood lipids between resistance trained athletes who use anabolic steroids and those who do not, and to compare them to university cross country athletes. METHODS–Four groups of men were evaluated: recreational lifters, n = 11, lifting < 10 h.week-1; heavy lifters, n = 16, lifting > 10 h.week-1; steroid users, n = 8, same as heavy lifters and used steroids; runners, n = 8, university track members. Echocardiograms, body composition (hydrostatic weighing), maximum oxygen consumption (Vo2), and lipids were studied. RESULTS–As expected, Vo2 (ml.kg-1.min-1), was greatest in the runners, with no difference among the lifting groups. High density lipoprotein cholesterol in the steroid user group was lower than in heavy lifters or runners. Left ventricular internal diastolic dimension was similar among the groups. The left ventricular mass index of the steroid user group was significantly greater than recreational lifters, at 161 v 103. There was no difference among heavy lifters (127), runners (124), and steroid users. There was no compromise in diastolic function in any group. There were no differences among groups in resting or exercise blood pressure. CONCLUSIONS–Resistance training in the absence of steroid use results in the same positive effects on cardiac dimensions, diastolic function, and blood lipids as aerobic training.